Differently sized cuckoos pose different threats to hosts. Issue 3 (8th October 2019) - Yu, Jiangping; E, Mingju; Sun, Wei; Liang, Wei; Wang, Haitao; Møller, Anders Pape
Abstract: Hole-nesting tits Parus spp. have been classified as "unsuitable" hosts for cuckoo parasitism because cuckoos cannot enter a cavity if the entrance is too small. However, Chinese tits could reject alien eggs and egg ejection rate increased with the local diversity of parasitic cuckoo species. Antiparasitic behavior among Chinese tits may have evolved due to greater size variation among sympatric cuckoo species. This raises the question of whether differently sized parasitic cuckoos pose different threats to Chinese tits. A green-backed tit Parus monticolus population that is sympatric with Asian emerald cuckoo Chrysococcyx maculatus (eme-cuckoo, small-sized parasite) and common cuckoo Cuculus canorus (com-cuckoo, large-sized parasite), and a cinereous tit P. cinereus population that is only sympatric with com-cuckoo were chosen as study organisms. We observed behavioral response and recorded alarm calls of the 2 tit species to eme-cuckoo, com-cuckoo, chipmunk Tamias sibiricus (a nest predator) and dove Streptopelia orientalis (a harmless control), and subsequently played back alarm calls to conspecific incubating females. In dummy experiments, both tit species performed intense response behavior to chipmunk, but rarely responded strongly to the 3 avian species. In playback experiments, both tit species responded strongly to conspecific chipmunk alarm calls, but rarely responded to dove alarm calls. The intensity of response of incubating female green-backed tits to eme-cuckoo and com-cuckoo alarm calls were similar to that of chipmunk alarm calls, while the intensity to eme-cuckoo alarm calls was higher than the intensity to dove alarm calls which was similar to that of com-cuckoo alarm calls. In contrast, few female cinereous tits responded to eme-cuckoo and com-cuckoo alarm calls. These findings indicated that the threat level of eme-cuckoo was slightly greater than that of com-cuckoo for sympatric green-backed tits, but not for allopatric cinereous tits.